2021
DOI: 10.5187/jast.2021.e14
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and microbial characteristics of longissimus lumborum and biceps femoris muscles in Korean native black goat with wet-aging time

Abstract: This study examined the effects of different wet-aging times on the physicochemical characteristics and microbial profile of longissimus lumborum (LL) and biceps femoris (BF) muscles from Korean native black goat (KNBG) meat. The water holding capacity (WHC), pH, cooking loss, shear force, meat color, free amino acid, total bacteria, and coliform count of KNGB meat were analyzed at 0, 5, 10, and 15 days of wet-aging at 4°C under vacuum packaging. The results showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 32 publications
4
8
0
Order By: Relevance
“…However, on day 21, the TAC values of all samples were 7.46, indicating unacceptable meats. The levels of bacterial counts throughout the 14 days of storage in the present study were consistent with Ali et al (2021) and Sabow et al (2016) , who reported these values in wet-aged goat meat. For the effect of enzymes, B13- and S6-treated samples showed a higher TAC value than the control (p<0.05).…”
Section: Resultssupporting
confidence: 92%
“…However, on day 21, the TAC values of all samples were 7.46, indicating unacceptable meats. The levels of bacterial counts throughout the 14 days of storage in the present study were consistent with Ali et al (2021) and Sabow et al (2016) , who reported these values in wet-aged goat meat. For the effect of enzymes, B13- and S6-treated samples showed a higher TAC value than the control (p<0.05).…”
Section: Resultssupporting
confidence: 92%
“…However, in previous study by Ali et al [ 7 ] it has beee explained that the taste, flavor, texture, and other physicochemical characteristics of meat vary on different muscle cuts depending on the muscle types. Also, free fatty acids releases due to the degradation of muscle lipids producing peroxidase which reacts with peptides to form the aroma compounds [ 8 ].…”
Section: Introductionmentioning
confidence: 98%
“…BF contains more type I muscle fibers than longissimus dorsi , giving it a higher red color intensity ( Ismail et al, 2019 ). The BF also exhibits a high free amino acid (FAA) content and water holding capacity, making it suitable for roast and grill cooking ( Ali et al, 2021 ; Ismail et al, 2019 ). Notably, lysine (Lys) and alanine (Ala) were found to be predominant amino acids in BF, contributing to its salty and sweet taste, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, lysine (Lys) and alanine (Ala) were found to be predominant amino acids in BF, contributing to its salty and sweet taste, respectively. Furthermore, BF from goats had a higher taurine (Tau) content, making it an appealing option for health-conscious consumers ( Ali et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%